Roll me up and smoke me when I die musings from the road - Nelson, Willie 1933- (William Morrow, 2012)
America's greatest traveling bard Willie Nelson muses about the things that are most important to him and celebrates the family, friends, and colleagues who have blessed his remarkable journey
Keywords: Nelson, Willie / 1933-; Nelson, Willie -- 1933-; Geschichte 1933-2012; Country musicians / United States / Biography; Country-Musiker; USA; Autobiografie